NiTi Intermetallic Surface Coatings by Laser Metal Deposition for Improving Wear Properties of Ti-6Al-4V Substrates. (17th March 2014) - Mokgalaka, Mokgadi Nomsa; Pityana, Sisa Lesley; Popoola, Patricia Abimbola Idowu; Mathebula, Tebogo
Abstract : The NiTi intermetallic possesses a number of good properties, such as high wear, oxidation, and corrosion resistance. This paper focuses on the deposition of NiTi intermetallic coatings on Ti6Al4V substrate by laser melting of Ti and Ni elemental powder mixtures. The effect of varying the Ti content in the NiTi composition on the microstructure and wear properties of the coatings was investigated. The microstructure of the NiTi intermetallic coatings were characterized by the scanning electron microscope (SEM) equipped with Energy Dispersive Spectroscope (EDS). The wear properties of the coatings were performed under accelerated dry sliding wear tests. The results obtained from the SEM/EDS analysis; show that the coatings consist of Ni and Ti elements from the feedstock, and the NiTi, NiTi2 and NiTi3, intermetallic phases. Dry sliding wear analysis revealed that there is correlation between the hardness and the wear rate. The coatings displayed significant improvement in wear resistance up to 80% compared to the substrate.